Design of a Building Connection Bridge at the Main Plaza of Al-Amin Living Lab and Industrial Park in Sampe Cita Village, Kutalimbaru District - Dara Wisdianti; Novalinda; Faurantia Forlana Sigit; Ida Khairani Siregar (International Forum of Researchers and Lecturers, 2024)
The design of the building connection bridge at the main plaza is a crucial step in urban infrastructure development, allowing pedestrians to move safely and efficiently between various key points within an area. This study aims to understand the design of the building connection bridge at the main plaza of Al-Amin Living Lab and Industrial Park in Sampe Cita Village, Kutalimbaru District, and its function for pedestrians. The research material focuses on the site location in Sampe Cita Village, Kutalimbaru District, Deli Serdang Regency, with observed parameters being the physical condition of the design location and the non-physical condition. The results of this study explain that the facilities and infrastructure of the Mixed-Use Building Connection Bridge at Al-Amin Living Lab and Industrial Park consist of circulation connecting the Mixed-Use buildings and a Viewing Deck and that the design guidelines for the Mixed-Use buildings at Al-Amin Living Lab and Industrial Park have met the criteria.